The Effect of Organizational Culture, Leadership and Compensation Towards Motivation and Organization Commitment In PT. Andalas Karya Mulia Pekanbaru - Yannie Warsita; Zulfadil Zulfadil; Susi Hendriani (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
The purpose of this study was to examine the influence of organizational culture, leadership and compensation on motivation, organizational culture, leadership, compensation and motivation on organizational commitment, and the influence organizational culture, leadership and compensation on organizational commitment mediated by motivation. The Population of this research was 137 people. Meanwhile the samples of this study were 102 respondents which were determined based on the slovin formula. The data used in this study is the primary data with data collection techniques are interviews and questionnaires, and to prove the result of this research using Structure Equation Modell (SEM) with a program tool namely Partial Least Square (PLS). The results of this research showed that organizational culture had a positive but not significant effects on motivation, leadership and compensation had significant positive effects on motivation, organizational culture, compensation and motivation had significant effects on organizational commitment, leadership had a positive but not significant effects on organizational commitment and organizational culture and motivation had significant positive effect on commitment organization and are fully mediated by motivation. The empiric finding, indicated that to increase organizational commitment need to pay attention to factors that influencing organizational commitment such as motivation, organizational culture, leadership and compensation.